Implementasi Merdeka Belajar Dalam Mata Pelajaran Pendidikan Agama Islam Untuk Meningkatkan Sikap Religius Siswa - Basri, Junaidin; Salamudin, Ceceng; Azizah, Umi (STAI Al-Musaddadiyah Garut, 2023)
This research stems from societal and cultural phenomena, namely youth violence, trends towards casual sex, and the abuse of narcotics and other addictive substances. Addressing these moral issues among adolescents, the government has introduced the